Vitamin D Deficiency Is Associated with the Presence and Severity of Diabetic Retinopathy in Type 2 Diabetes Mellitus. (20th May 2015) - Alcubierre, Nuria; Valls, Joan; Rubinat, Esther; Cao, Gonzalo; Esquerda, Aureli; Traveset, Alicia; Granado-Casas, Minerva; Jurjo, Carmen; Mauricio, Didac
Abstract : There is very few evidences on the role of vitamin D in the development of diabetic retinopathy. The aim of the current study was to explore whether there is an association of vitamin D status and diabetic retinopathy in type 2 diabetes. Two groups of patients were selected: 139 and 144 patients with and without retinopathy, respectively, as assessed by an experienced ophthalmologist. Subjects with advanced late diabetic complications were excluded to avoid confounding biases. 25-Hydroxy-vitamin D3 (25(OH)D) concentrations and vitamin D deficiency were associated with the presence of diabetic retinopathy. Additionally, patients with more advanced stages of retinopathy (grades 2–4) had lower concentrations of 25(OH)D and were more frequently vitamin D deficient as compared with patients not carrying this eye complication. In conclusion, our study confirms the association of vitamin D deficiency with the presence and severity of diabetic retinopathy in type 2 diabetes. Further experimental and prospective studies on this issue are clearly warranted.